Prevalence and diagnostic efficacy of trans-abdominal and trans-vaginal ultrasound for ectopic pregnancies: a longitudinal study - Shakeel, Isha; Shabbir, Ahmad; Yumn, Laiba; Akhtar, Mariyam; Khan, Esha; Khan, Ali Ahmad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Reducing maternal mortality and morbidity requires an accurate diagnosis of ectopic pregnancy. The fallopian tube is the most frequent location for ectopic pregnancy. Methods: This study was based on a longitudinal analytical design conducted at tertiary care hospitals in Pakistan. Patients in the reproductive age range (20 to 32 years) who underwent clinical examination and investigations and were diagnosed with ectopic pregnancy were included in this study. The ultrasound results of all the patients were evaluated, and data was collected on the existence and positioning of an ectopic pregnancy. Results: In the study, 198 women underwent TVS and TAS. At the time of diagnosis, the age range was 20-32 years old. Our study found that 2.5% of pregnancies resulted in an ectopic pregnancy. 20 women had symptomatic EP that was confirmed. For the initial TVUS, the sensitivity and specificity of ultrasonography were 88.5% and 96.5%, respectively, and with a second rescan, they were 93.1% and 95.7%. Conclusions: Our study showed that an excellent method for identifying ectopic pregnancy is trans-abdominal ultrasonography. Regarding diagnostic accuracy metrics, however, it falls short of trans-vaginal ultrasound. To avoid missing any cases of ectopic pregnancy, early detection can significantly reduce morbidity and mortality. We should employ both ultrasonography modalities sequentially, with TAS being used first.